Hesperidin as Radioprotector against Radiation-induced Lung Damage in Rat: A Histopathological Study - Haddadi, Gholam Hassan (J Med Phys, 2017)
Reactive oxygen species (ROS) are generated by ionizing radiation, and one of the organs commonly affected by ROS is the lung. Radiation-induced lung injury including pneumonia and lung fibrosis is a dose-limiting factor in radiotherapy (RT) of patients with thorax irradiation. Administration of antioxidants has been proved to protect against ROS. The present study was aimed to assess the protective effect of hesperidin (HES) against radiation-induced lung injury of male rats. Fifty rats were divided into three groups. G1: Received no HES and radiation (sham). G2: Underwent γ-irradiation to the thorax. G3: Received HES and underwent γ-irradiation. The rats were exposed to a single dose of 18 Gy using cobalt-60 unit and were administered HES (100 mg/kg) for 7 days before irradiation. Histopathological analysis was performed 24 h and 8 weeks after RT. Histopathological results in 24 h showed radiation-induced inflammation and presence of more inflammatory cells as compared to G1 (P < 0.05). Administration of HES significantly decreased such an effect when compared to G2 (P < 0.05). Histopathological evaluation in 8 weeks showed a significant increase in mast cells, inflammation, inflammatory cells, alveolar thickness, vascular thickness, pulmonary edema, and fibrosis in G2 when compared to G1 (P < 0.05). HES significantly decreased inflammatory response, fibrosis, and mast cells when compared to G2 (P < 0.05). Administration of HES resulted in decreased radiation pneumonitis and radiation fibrosis in the lung tissue. Thus, the present study showed HES to be an efficient radioprotector against radiation-induced damage in the lung of tissue rats.